Relationship Between History of Hormonal Contraception with Hormonal Receptor’s Expression on Breast Cancer Patients in Mohammad Hoesin General Hospital Palembang - Al Maududy; Halbana; Mulawan Umar; Bahar Erial (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2021)
Background: Cancers with esterogen receptor negative (ER-) have a worse prognostic than estrogen receptor positive (ER +). Research by Cooper at al and Huiyan Ma et al have found strong association between history of hormonal contraceptive use and breast cancer with receptor negative estrogen (ER -). However, another study from Cotterchio et al found no difference. Methods: This study investigated breast cancer patients who went to dr. Moh Hoesin Palembang. This study involved 200 respondents with data obtained using patient immunohistochemical data and interviews using a questionnaire. This study uses a cross sectional analysis method. Data were obtained from the history of use of hormonal contraception, the type of hormonal contraception, and the status of hormonal receptors (Esterogen Receptors (ER) and Progesterone receptors (PR). 2x2 tables were used to obtain the Prevalence Ratio (PRR) and chi quare to obtain p values. Results: The results of the Chi square analysis showed that there was no significant relationship between the history of hormonal contraception and negative receptor expression with the prevalence ratio of hormonal contraceptives and ER (-) 1.48 times and PR (-) 1.43 times. There was no significant relationship between type of contraception and negative ER PR. The highest relative risk is in implant contraception with 1.54 times for ER (-) and 1.8 times for PR (-) Conclusion: There was no relationship between the history of hormonal contraception and negative hormonal receptors